Fintech’s game-changing opportunities for SMEs: A study on selected SMEs in Bangladesh - Hoque, Md. Ariful (Asian Economic and Financial Review, 2023)
The growth of a developing economy, such as that of Bangladesh, relies on its small and medium-sized enterprises (SMEs) as they account for more than 25% of the country’s gross domestic product (GDP). The present study assesses the impact of financial technology (fintech) on the growth of SMEs in Bangladesh. A structured questionnaire was developed and used to collect primary data from 77 respondents who work at 10 selected SMEs. Fintech products, especially mobile money, digital lending and mobile or online banking, are used as explanatory variables, while the growth of SMEs is the response variable. IBM SPSS was used to analyze the collected data, and regression analysis was used to assess the effect of fintech on the growth of SMEs in Bangladesh. Mobile money and mobile or online banking were found to have a statistically significant impact on SME growth, while digital lending did not. Therefore, fintech service providers should increase efforts to advertise their products to encourage more merchants to use them. This is the only study to date that conclusively proves that fintech products, especially mobile money and mobile or online banking, significantly affect SME growth in Bangladesh.